Industrial Wastewater Treatment and Sanitary Management System Optimization for Class III Water discharge from pithead level 250 (EF 03) to the San José River, Peru - Puente Rodríguez, Adán (2018)
The main objective was to manage the implementation of standards, procedures and legal requirements in order to optimize the industrial wastewater treatment system of the Huarón Mine in Peru. Furthermore, to ensure the quality of class III water discharges. The results obtained were satisfactory; a final pH of 8.02 with a dosage of 100 gr/m3 (Cal) and a reduction of zinc metal content below 2.5 ppm were achieved.